Comparative analyses of responsiveness between the Rheumatoid Arthritis Impact of Disease score, other patient-reported outcomes and disease activity measures: secondary analyses from the ARCTIC study. Issue 2 (26th October 2018) - Holten, Karen; Sexton, Joseph; Kvien, Tore K; Aga, Anna-Birgitte; Haavardsholm, Espen A
Abstract : Objective: To evaluate the responsiveness of the Rheumatoid Arthritis Impact of Disease (RAID) score compared with other patient-reported outcome measures (PROMs), inflammatory markers and clinical disease activity measures in patients with early rheumatoid arthritis (RA). Methods: Disease-modifying antirheumatic drug–naïve patients with RA with short disease duration were included in the treat-to-target ARCTIC trial and followed for 24 months. The responsiveness of the RAID score was evaluated using standardised response mean (SRM) and relative efficiency (RE) with respect to tender joints by Ritchie Articular Index (RAI). SRMs and REs were also calculated for other PROMs, inflammatory markers and clinical outcome measures. An SRM with value above 0.80 was considered high. Results: 230 patients with RA were included. The mean±SD symptom duration was 7.1±5.4 months and the baseline mean±SD RAID score was 4.49±2.14. At 3 months of follow-up, the mean±SD change score for RAID was −2.25±1.98 and the SRM (95% CI) −1.13 (−1.33 to −0.96). The RAID score showed high responsiveness both at 3 and 6 months (SRM≥0.80) and was more sensitive in detecting change than the reference, tender joints assessed by RAI. Conclusions: The RAID score proved to be highly responsive to change in patients with RA with short disease duration who followed a treat-to-target strategy. The RAID score was more efficient in detecting change than the reference (RAI) as well as most other PROMs.